Actividad inhibidora in vitro sobre α-glucosidasa de tres extractos de plantas de uso medicinal, Iquitos 2019 - Cueva Piña, Jorge (2021)
The objective of this research was to evaluate the in vitro inhibitory effect on ?-glucosidase of three plant extracts for medicinal use. Being the main objective to determine the molecules that cause the inhibitory activity of the three plant species and the percentage of inhibition of the extracts in vitro on ?-glucosidase, the samples were collected in the Arboretum of the IIAP in Jenaro Herrera and the Botanical Garden of the IMET, subsequently dried at 40°C and micropulverized for the preparation of methanolic extracts (macerated for 7 days). The ?-glucosidase enzyme inhibition assay was developed according to the method proposed by Artanti et al. 2012 and Srianta et al. 2013 and to obtain the data of the molecules, they were sent to the Institute of Biochemistry and Molecular Biology of the UNALM, for which a gas chromatography coupled to mass spectrophotometry (CG-MS) equipment was used. The species Coussapoa asperifolia "Renaco caspi" showed the highest percentage of inhibition and an IC50 of 50.22 ?g/mL. In this way, it was concluded that the species Remijia pedunculata "Chullachaqui caspi" and Myrciaria dubia "camu camu" reported lower values in ?-glucosidase inhibition but are within the range of antihyperglycemic activity. The most abundant molecules present were 2,2?-methylene bis[6-(1,1-dimethyl ethyl)-4-methyl- phenol followed by diisoctyl 1,2--benzenedicarboxylate, 1,2-dihydro-2 ,2,4- trimethyl quinoline.